Optimization of Swimming Education in Physical Education at Schools: A Systematic Literature Review in Indonesia - Lusianti, Septiyaning (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2024)
This study explores the challenges and solutions in swimming education within physical education in Indonesian schools through a Systematic Literature Review (SLR) method. The literature review reveals several major issues impacting swimming education, including limited facilities, lack of teacher training and certification, and constrained curriculum time. Limited facilities, especially in rural areas, result in insufficient access for students to learn swimming effectively. Furthermore, many teachers lack specific competencies in teaching swimming, reducing the effectiveness of the instruction. Low societal awareness about the importance of swimming and minimal government support also contribute to these challenges. To address these issues, it is recommended to enhance facilities in schools, implement specialized training programs for teachers, adjust the curriculum to provide more time for swimming instruction, increase public awareness, and secure stronger government support. These measures are expected to optimize swimming education in physical education and provide greater benefits for students